Respuesta :
Answer:
3rd one. The general form of a circle is set equal to the radius squared. So right side is 4 then plug in values until true.
Answer:
The answer is the second option
[tex](x-1)^{2}+(y-4)^{2}= 4[/tex]
Step-by-step explanation:
The general equation of a circle is:
[tex](x-h)^{2}+(y-k)^{2}= r^{2}[/tex]
in this equation (h,k) is the center of the circle and r is the radius, so if the center is in (1,4) and the radius is 2, the values of the constants are:
h = 1
k = 4
r = 2
And the formula for this circle is:
[tex](x-1)^{2}+(y-4)^{2}= 2^{2}[/tex]
[tex](x-1)^{2}+(y-4)^{2}= 4[/tex]